Pelatihan Pembuatan Ecoprint untuk Meningkatkan Literasi Sains Siswa di Pesantren Al-Manar Aceh Besar - Ulia Hanum; Mauizah Hasanah; Meutia Zahara; Qurrati Aini; Cut Novrita Rizki; Suwarniati Suwarniati; Fatemah Rosma; Nurul Fajriana; Muslich Hidayat; Diannita Harahap; Raudhah Hayatillah; Manja Manja; Syakia Tursina (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2026)
A well-prepared community service activity introduces beneficial knowledge to the target community while contributing to students' scientific literacy. This activity aimed to train students at Pesantren Al-Manar, Aceh Besar, in making ecoprint as an alternative natural dyeing technique and to improve their scientific literacy. Ecoprint is a fabric-printing technique that transfers natural pigments from leaves and flowers onto cloth through direct contact, commonly applied using the pounding (hapazome) or steaming method. The activity was carried out for five days, from 26 to 30 May 2023, at Pesantren Modern Al-Manar, Lampermai Village, Aceh Besar, and involved 20 seventh-grade students of MTs Al-Manar. The methods used were lectures, demonstrations, group discussions, and presentations, in which students practiced applying leaves and flowers onto plain white fabric and tote bags. The results showed that the training ran smoothly and was well received, giving students new knowledge about ecoprint as an environmentally friendly, natural alternative to synthetic dyes, while also fostering their creativity and entrepreneurial spirit.